Non-extraction camouflage treatment using extra-alveolar skeletal anchorage - Lee Young-Jun; Park Jae Hyun; Chang Na-Young; Lee Kang-Gyu; Chae Jong-Moon (Sciendo, 2022)
A 23-year-old female patient with moderate crowding and a bilateral molar scissor-bite was successfully treated without tooth extraction. Extra-alveolar skeletal anchorage, involving a three-dimensional key plate in the maxilla and two miniscrews in the buccal shelf of the mandible, were used for distalisation, buccolingual uprighting, and the intrusion of molars by fixed orthodontic appliances. Cone-beam computed tomography was used to identify available posterior space for the distalisation and buccolingual correction of the molars in scissor-bite. The total treatment time was 24 months. Post-treatment results showed good occlusal relationships and smile aesthetics. Twelve-month post-treatment records demonstrated no significant relapse and a favourable facial balance.